Hubungan Perilaku Dengan Kebiasaan Jajan Siswa Di Kantin Sekolah Menengah Pertama (SMP) 37 Kecamatan Kindang Kabupaten Bulukumba - Ulul Azmiyani Yasir; Nurbaeti; Andi Mansyur Sulolipu; Andi Asrina; Farihah Muhsanah (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2026)
Food safety is a significant public health issue, particularly among school-aged children who frequently consume snacks in school settings. Poor snack choices can increase the risk of consuming unsafe food, thereby impacting health. This study aimed to analyze the relationships among knowledge, attitudes, and pocket money and students' snacking habits. A quantitative approach with a cross-sectional design was employed. Data were collected via questionnaires from 70 students at SMP 37 Bulukumba and analyzed using the chi-square test at a significance level of α = 0.05. The results revealed a significant relationship between knowledge and snacking habits (p = 0.000); the majority of respondents with poor knowledge exhibited poor snacking habits (93.3%). A significant relationship was also found between attitudes and snacking habits (p = 0.002), with most respondents holding poor attitudes displaying poor snacking habits (88.4%). Furthermore, a significant relationship was observed between pocket money and snacking habits (p = 0.004). In conclusion, knowledge, attitudes, and pocket money are associated with students' snacking habits. Schools are encouraged to enhance education on selecting safe and healthy snacks and to foster a school food environment that supports healthy snacking behaviors.